Prevalence of SARS-CoV-2 in newborns born to SARS-CoV-2-positive mothers at 2 weeks of life - Jan, Sophia; Katz, Robert; Fagan, David; Santos, Telmo; Beachy, Joanna C.; Steinway, Caren; Chen, Jack; Tsouristakis, Alina; Mancenido, Briana; Leung, Christy; Moore, Emily; Wilson, Estelle; et al. (Frontiers in Pediatrics, 2024)
Introduction: Limited evidence exists on management recommendations for neonates born to SARS-CoV-2 positive mothers. This study looked at transmission risk of neonates presenting for primary care in a large regional health system within New York during the early months of the COVID-19 pandemic.This was prospective, observational study of newborns of SARS-CoV-2 positive mothers presenting at any of the 19 Northwell Health-Cohen Children's Medical Center (CCMC) primary care practices who underwent another oropharyngeal/nasopharyngeal swab for detection of SARS-CoV-2 by DOL 14.Results: Among 293 newborns of SARS-CoV-2 positive mothers that were negative at birth, 222 were retested at 14 days of life, corresponding to times with different predominant strains. Of these, 7 tested positive but had no symptoms.The overall low transmission rates and absence of symptomatic infection support the safety of direct breastfeeding after hospital discharge with appropriate hand and breast hygiene.